(untitled) (Revista de Ciências Agroveterinárias, 2024)
Hemoparasite infections are a substantial challenge to agriculture, worldwide. Infected cattle suffer malnutrition, stunting, decreased milk production, and reproductive loss, which can result in great economic loss. The aim of this study was to characterize the predominant hemoparasites affecting cattle in Nicaragua, whose economy is largely dependent on agriculture, and define associated epidemiological factors. Blood from 68 bovines in the municipality of León were analyzed by microscopy and molecular techniques. PCR revealed Anaplasma marginale in 33.82% (IC 95%: 21.84-45.80), 19.11% (IC 95%: 9.03-29.19) of animals were infected with Babesia spp, and 8.82% (95% CI: 1.34-16.30) were simultaneously co-infected with Babesia spp and A. marginale. However, A. phagocytophilum, Leishmania spp., or Trypanosoma spp were not detected (0%, 95% CI: 0.0-5.20). A. marginale was more frequently detected in males (p=0.041) and calves (p=0.041). This is the first study to report the prevalence of hemoparasites in cattle using molecular diagnosis in western Nicaragua.